Skin inspired thermoresponsive polymer for constructing self-cooling system. (15th February 2022) - Ji, Yating; Sun, Yilan; Javed, Muhammad; Xiao, Yonghe; Li, Xiaoyan; Jin, Kaili; Cai, Zaisheng; Xu, Bi
Graphical abstract: Highlights: A self-adaptive passive cooling material is prepared. Poly(N-isopropylacrylamide) and calcium alginate contribute to the passive cooling. A temperature reduction of ∼13 ℃ was achieved in outdoor practical application. The prepared passive cooling material shows superior reusability. Abstract: Excessive building energy consumption is one of the grand challenges for the human. In this work, a passive cooling fabric which is inspired by skin sweating has been proposed by depositing a thermoresponsive hydrogel on the cotton. The obtained composite hydrogel exhibits a porous structure and shows a hygroscopicity of ∼1.71 g/g, providing excellent heat dissipation by evaporating water. The results show that a cooling effect of ∼13 °C could be achieved in outdoor practical applications. Additionally, the influencing factors of hygroscopicity and structure stability of the hydrogel were also investigated. This self-adaptive material can effectively absorb moisture at night and realize cooling by releasing water in the daytime. The research results suggest that the skin-inspired passive cooling material provides another strategy to alleviate the shortage of power resources and meet the needs of thermal management.